A critical analysis of conflicts between herdsmen and farmers in Nigeria: Causes and socioreligious and political effects on national development - Ndubuisi, Christopher I. (HTS teologiese studies, 2018)
The Fulani herdsmen attack on Nigerian citizens has taken on an alarming dimension this day. Hardly a week passes without one rumour of attack or another in one part of the country. In each of these attacks property worth millions of naira and lives are destroyed on a large scale. The huge human loss is the most worrisome of all. The objective of this study is to discuss the causes, as well as the socio-economic, political and religious implications of these attacks for sustainable development. The study adopted qualitative and phenomenological approaches in its investigation and analysis of data drawn from existing literature and oral interviews with selected individuals. The study discovered that many people have lost their property and lives; that many people have been displaced from their homes; and that the peace, security and unity of the country as a federation are being seriously threatened.